The effects of private versus public health insurance on health and labor market outcomes - Christine Dauth (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2021)
Among health care systems with both public and private elements (such as in the US and Germany), an important question is whether the type of health insurance exerts an impact on workers' careers. We exploit the unique German case of a two-tier health care system to analyze whether opting out of public statutory health insurance and into private health insurance affects the specific health and employment outcomes of employed workers over a period of nine years. We exploit administrative registers and apply a fuzzy regression discontinuity design. We do not find any evidence that the type of health insurance affects employed workers' outcomes in the medium or long run. This suggests that even though private health insurance entails more comfortable healthcare conditions, public health insurance does not come with heavy health impairments or detrimental employment outcomes. – – In Gesundheitssystemen mit gesetzlichen und privaten Krankenversicherungen (so wie beispielsweise in den USA oder in Deutschland), stellt sich die Frage, ob die Art der Krankenversicherung die Arbeitsmarktkarrieren der Versicherten beeinflusst. Wir untersuchen, ob der Wechsel von der gesetzlichen in die private Krankenversicherung bestimmte Gesundheits- und Beschäftigungsvariablen über einen Zeitraum von neun Jahren beeinflusst. Wir nutzen administrative Prozessdaten und verwenden ein Fuzzy Regression Discontinuity Design um kausale Effekte zu identifizieren. Wir finden keinerlei Hinweise auf einen mittel- oder langfristigen Einfluss der Art der Krankenversicherung auf lange Krankheitsepisoden oder den Arbeitsmarkterfolg von Beschäftigten. Dies deutet darauf hin, dass eine Mitgliedschaft in der privaten Krankenversicherung zwar mit mehr Annehmlichkeiten verbunden ist, aber nicht mit gravierenden Nachteilen bei der Gesundheit oder dem Arbeitsmarkterfolg.
Keywords: I13; J21; J30; 330; Employment; fuzzy RDD; health instrumental variables; labor market outcomes; private health insurance; public health insurance